Self-Efficacy as the Strongest Predictor of Adolescent Reproductive Health Behavior: A Health Belief Model Study among Vocational Students in Rural East Java - Kustin Kustin; Lailatul Rahmawati; Firda Ayu Anugrah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Adolescents enrolled in vocational high schools, especially in rural areas, are particularly susceptible to reproductive health risks due to limited knowledge, low perception of risk, and restricted access to reliable information. The health belief model presents a comprehensive theoretical framework to explain these behavioural determinants. This study explores the factors influencing reproductive health behaviour among vocational high school students in rural areas of East Java, IndonesiaMethod: A school-based cross-sectional study design was used, with 150 students chosen through random sampling. Data were obtained through a structured questionnaire and subsequently analysed using Chi-square tests and multivariate logistic regression.Result: The findings indicated that all constructs of the Health Belief Model—perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy—were significantly related to reproductive health behaviour (p < 0.05). Students with higher perceived susceptibility and perceived benefits, lower perceived barriers, and greater self-efficacy were more likely to engage in positive behaviours. In the adjusted analysis, self-efficacy emerged as the most dominant predictor (OR = 3.85; 95% CI: 2.01–7.39; p < 0.001). Perceived susceptibility, perceived benefits, perceived barriers, and cues to action remained independently associated, whereas perceived severity showed a relatively weaker effect. These findings highlight the critical role of cognitive and perceptual factors in shaping adolescents’ reproductive health behaviour within vocational school settings. Interventions based on the Health Belief Model—particularly those aimed at enhancing self-efficacy and reducing perceived barriers—are essential for enhancing reproductive health outcomes among adolescents in underserved rural area. Keywords: Adolescent reproductive health. Health belief model, Health behavior, Secondary school students